Using iso 9001 to Improve Sales Operation Performance: A Case Study of Implementationf ISO 9001 - Sumaedi, Sik (Universitas Prasetiya Mulya, 2009)
This study aims to examine the implementation of ISO 9001 in order to improve the sales operation performance of a management training and consultancy company. More specifically, this research is to identify the performance indicators of the company sales operation, ISO 9001based sales operation management systems, and the comparison of the sales operation performance before and after the implementation of the model. This study is an action research using descriptive case study. The research results show the sales operation performance indicators and ISO 9001based sales operation management system model. In addition, the finding of this study indicates that the use of ISO 9001 can improve the performance indicators of sales operation, such as response speed, the number of prospective customers, customer retention and the number of new customers.